(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The larger share of Beedi workers in India belong to the unorganized sector. The workers in this sector are facing innumerable issueslike poor working condition, low wages, fraud by contractors and various other health hazards. They are basically from the weakersection of the society. In order to ameliorate their condition, the government has initiated various welfare legislations and enactedvarious schemes to give them better life and thereby trying to improve their standard of living. These Acts and schemes provide forvarious social security provisions like easy access to medical treatment, access to education, subsidised housing and entertainmentfacilities, etc. But in spite of the legislations and various schemes, the condition of the workers is far from satisfactory as they cannotreap the benefits given for them under those enactments. In order to deal with all the difficulties, government must take steps foruplifting this section of the society. This paper is an attempt to study the socio-economic conditions of the beedi workers in India andto suggest fruitful measures for effective enforcement and implementation of the social welfare legislations and schemes in favour ofthe beedi workers in India.